2009
DOI: 10.1590/s1413-81232009000200009
|View full text |Cite
|
Sign up to set email alerts
|

Uma perspectiva psicossocial da sintomatologia depressiva na adolescência

Abstract: Resumo Este trabalho objetivou apreender as representações sociais (RS) da depressão entre adoles-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
0
4
0
7
Order By: Relevance
“…In a study of teenagers regarding the social representations of depression, Aragão et al observed that women express depression through pain, sadness, and unhappiness and describe a depressed person as someone who is in crisis. By contrast, men associate depression with anger and describe depressed people as lonely (Aragão, Coutinho, Araújo, & Castanha, 2009).…”
Section: Psychology Health and Medicine 139mentioning
confidence: 97%
“…In a study of teenagers regarding the social representations of depression, Aragão et al observed that women express depression through pain, sadness, and unhappiness and describe a depressed person as someone who is in crisis. By contrast, men associate depression with anger and describe depressed people as lonely (Aragão, Coutinho, Araújo, & Castanha, 2009).…”
Section: Psychology Health and Medicine 139mentioning
confidence: 97%
“…It may also be justified by the way each gender represents its depressive state. Aragão et al (2009), when researching about social representations of depression in adolescents, concluded that women represented depression through pain, sadness, unhappiness and described depressed people as worried, while men associated depression with anger and described depressed people as solitary. This reinforces the idea of depression manifesting itself in women in a more internalized form, while predominantly externalized in men.…”
Section: Discussionmentioning
confidence: 99%
“…Aragão, Coutinho, Araújo, and Castanha (2009) found that both genders have different social representations of depression. Therefore, their experience of it may also be different.…”
Section: Methodsmentioning
confidence: 99%
“…Os artigos analisados foram agrupados em 4 seções de acordo com o objetivo central: a) depressão 12,18,19,22,30,31 ; b) depressão e drogas 13,26,33 ; c) epidemiologia álcool e outras drogas [3][4][5]8,9,17,20,21,[23][24][25]28,32 ; d) uso de álcool e de outras drogas 27,29 .…”
Section: Autorunclassified